STATE AID AND FAIR COMPETITION - Nikolić, Ljubica (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
State aid (giving economic advantage to certain economic entities or groups of economic entities by granting subsidies and loans under more favorable conditions, state guarantees, tax breaks and tax exemptions, selling public property under particularly favorable conditions, etc.) may be economically justifiable but entails the risk of distortions of market competition. The EU has strict rules in the area of providing and controlling state aid, which aim to minimize state aid while minimizing competition. Fulfilling some of the commitments undertaken in the EU accession process, the Republic of Serbia passed the State Aid Control Act in 2009, which ceased to be valid with the adoption of a new State Aid Control Act in 2019. The share of state aid in Serbia’s GDP is substantial but insufficiently transparent, which justifiably raises the issue of its impact on fair competition. The reform of the Serbian state aid policy is necessary, first and foremost, in order to significantly reduce this aid and to properly select the beneficiaries. The starting point for an effective state aid policy is legal regulation and its implementation but, above all, the genuine independence and responsibility of the institutions in charge of controlling its implementation. It is necessary to find modalities that will ensure that the general interest and economic efficiency are above individual interests. This paper aims to promote awareness about the impact of state aid on economic efficiency, to analyze the legal solutions and the institutional framework in this field in Serbia, and to present the EU state aid policy. The emergence of excessive, improperly selective and uncontrolled state aid can have profound negative consequences on social well-being, for which reason it is necessary to properly standardize and implement the rules envisaged in this area of law.